THE RATIONALITY OF FAITH: The Study of Abraham's Faith in Hebrews 11: 17-19 - Alexander Eduard Thodorus de Walick; Peni Hestiningrum (Scriptura Indonesia, 2021)
In Christian and church life, Faith and Rationality are often opposed to one another. Some Christians reject the aspect of rationality in doing theology, and vice versa. In the Bible presenting Abraham as an example of faith learning through his experiences when he was tempted to offer up Isaac to his only son, he was without a doubt prepared to carry out the commandments he received with a thoughtful attitude; that God is able to raise (Isaac) people even from the dead (Hebrews 11: 17-19). The research method used is exegetical study with background and grammatical contexts. The aim of this research is to find the meaning of Abraham's faith in Hebrews 11: 17-19. The result of this research is that the quality of faith is tested and that faith thinks rationally and continuously based on God's word.